Nanoenergy Nanotechnology Applied for Energy Production - de Souza, Flavio Leandro; Leite, Edson Roberto; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
Low dimensional systems have revolutionized the science and technology in several areas. However, their understanding is still a great challenge for the scientific community. Solar energy conversion devices based on nanostructured materials have shown exceptional gains in efficiency and stability. In this context, nanostructures allow an improvement of surface properties, transport and charge transfer, as well as direct application as sensors and storage devices and energy conversion. This book discuss the recent advances and future trends of the nanoscience in solar energy conversion and storage. It explores and discusses recent developments both in theory as well as in experimental studies and is of interest to materials scientists, chemists, physicists and engineers.
Preface -- Incorporation of inorganic nanoparticles in bulk heterojunction organic solar cells -- Nanomaterials for solar energy conversion: Dye-sensitized solar cells based on ruthenium(II) tris-heteroleptic compounds or natural dyes -- Facile routes to produce hematite film for hydrogen generation from photoelectrochemical water splitting -- Biofuel Cells: Bioelectrochemistry Applied to the Generation of Green Electricity -- Recent Advances on Nanostructured Eletrocatalysts for Oxygen Eletro-reduction and Ethanol Eletro-oxidation -- Nanocomposites from V2O5 and Lithium Ion Batteries -- Magnesium alloys as anode materials for Ni-MH batteries: Challenges and opportunities for nanotechnology.
Keywords: Engineering; Renewable energy sources; Optical materials; Engineering; Renewable and Green Energy; Nanotechnology and Microengineering; Optical and Electronic Materials